Foggy Scene Rendering Based on Transmission Map Estimation. (16th October 2014) - Guo, Fan; Tang, Jin; Xiao, Xiaoming
Abstract : Realistic rendering of foggy scene is important in game development and virtual reality. Traditional methods have many parameters to control or require a long time to compute, and they are usually limited to depicting a homogeneous fog without considering the foggy scene with heterogeneous fog. In this paper, a new rendering method based on transmission map estimation is proposed. We first generate perlin noise image as the density distribution texture of heterogeneous fog. Then we estimate the transmission map using the Markov random field (MRF) model and the bilateral filter. Finally, virtual foggy scene is realistically rendered with the generated perlin noise image and the transmission map according to the atmospheric scattering model. Experimental results show that the rendered results of our approach are quite satisfactory.